The Quantitative Methods in the Latin American Social Sciences - Cortés, Fernando (2008)
This text analyses how Statistics has been applied in sociological research during the last four decades, and its links to the main social and political processes. From the informed experience of the author, it distinguishes three moments: height, exile, resurgence.